2011
DOI: 10.1111/j.1471-0307.2011.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic lactobacilli on faecal enzyme and genotoxic activity in human faecal water in the presence of the carcinogen PhIP in vitro

Abstract: The average β‐glucuronidase activity for children was 0.48 ± 0.04 U/mg, for adults 0.75 ± 0.27 U/mg and for elderly 1.55 ± 0.06 U/mg. For β‐glucosidase, it was 0.19 ± 0.02 U/mg for children, 0.77 ± 0.26 U/mg for adults and 1.18 ± 0.27 U/mg for elderly. In the presence of probiotics, the highest decrease in genotoxicity was observed for Lactobacillus casei 0908 (to 7.99 ± 1.32) and Lactobacillus paracasei 0919 (to 6.19 ± 1.44) for all children. In adults, lower mean genotoxicity was regarded after incubation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…A large number of reports exist to describe the adsorption or the binding by lactic acid bacteria (LAB) of a variety of food-borne HCAs in vitro; in some of those studies, a concomitant decrease in mutagenicity was reported [4,8,11,16,17,19,25]. Nevertheless, nothing is known about direct toxic effects of HCAs on certain species of probiotic lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of reports exist to describe the adsorption or the binding by lactic acid bacteria (LAB) of a variety of food-borne HCAs in vitro; in some of those studies, a concomitant decrease in mutagenicity was reported [4,8,11,16,17,19,25]. Nevertheless, nothing is known about direct toxic effects of HCAs on certain species of probiotic lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…As a final note, the decrease of NDMA was dependent on the medium, incubation time, phase of growth, strain type, pH, and NDMA concentration (63). Degrading of two nitroso compounds, including diphenylnitrosamine (DPN) and 1-nitrosopyrrolidine (NPR) by three strains of L.plantarum was determined.…”
Section: Binding Ability Of Labs and Probiotics To Nitrosaminementioning
confidence: 99%
“…L. casei 0908 and L. paracasei 0919 were the most effective in decreasing genotoxicity in children and adults. In the elderly group, L. casei 0900 was the most efficient strains (63). In another study by Klewicka et al the protective effect of feeding beetroot juice fermented with Lactobacillus brevis 0944 and L. paracasei 0920 against aberrant crypt foci (ACF) formation in rat colon in the presence of PhIP.…”
mentioning
confidence: 99%
See 2 more Smart Citations